The Impact of Environmental Based Physics Learning on Students' Concept Mastery and Ecopreneurship Management - Titin Sunarti; Eko Hariyono; Woro Setyarsih; Binar Kurnia Prahani; S. Suyidno (IKIP Mataram, 2020)
Strengthening ecopreneurship plays an important role in preparing students for success in the life and career of students, but this skill is not well trained in learning physics. Therefore, the purpose of this study was to analyze the impact of environment-based physics learning on students' mastery of concepts and ecopreneurship. This research is a quasi experimental research with one group pretest and posttest design. The research subjects were 29 students of the physics education study program, Surabaya State University, Indonesia, who programmed basic physics courses. The data collection technique used a conceptual mastery test instrument and ecopreneurship. The data analysis technique used the Kolmogorov-Smirnov test, Paired t-test, Wilcoxon test, and N-Gain. The results showed a significant increase in students' mastery of concepts and ecopreneurship at α = 5%, with mean N-gain of 0.63 and 0.60, respectively, within the moderate criteria. Thus, environment-based physics learning has a significant impact on increasing student mastery of concepts and ecopreneurship.